Fearless women in the Mexican Revolution and the Spanish Civil War - Linhard, Tabea Alexa, 1972- (University of Missouri Press, 2005)
"Study of the role women played in the Mexican Revolution and the Spanish Civil War. Examines female figures such as the soldaderas of the Mexican Revolution and the milicianas of the Spanish Civil War and the intersection of gender, revolution, and culture in both the Mexican and the Spanish contexts"--Provided by publisher.